Weighted Approximation of $r$-Monotone Functions on the Real Line by Bernstein Operators (Analysis in Theory and Applications, 2011)
In this paper, we give error estimates for the weighted approximation of $r$-monotone functions on the real line with Freud weights by Bernstein-type operators.
Keywords: Freud weight; $r$-monotone function; Bernstein-type operator.